Early Jewish writings and New Testament interpretation - Elledge, Casey D. (Essentials of biblical studies, 2023)
"Early Jewish writings pose important implications for understanding the nature of "scripture" in ancient times, prior to the later formation of biblical canons. A review of early "non-canonical" literary collections unveils the diverse assumptions about "scripture" that existed within ancient Judaism. In their formative contexts, many of these writings present their religious claims as extensions of divine revelation, not merely as secondary, post-biblical compositions. Others endeavor to present themselves as essential complements to earlier scriptural books. Such high esteem for their authority appears to have been shared among some of their earliest audiences. Carefully studying the literature of this era, thus, reveals the extended horizon of authoritative traditions prevalent during the period of Christian origins. This realization arises from the modern study of literary collections known as Apocrypha (Deuterocanonical Books), Pseudepigrapha, Dead Sea Scrolls, and the writings of Philo and Josephus"--